Primary cardiac sarcoma: insights from two decades of multimodal management at LMU Munich - Anton Burkhard-Meier; Dorit Di Gioia; Vindi Jurinovic; Michael Hoberger; Sinan E. Güler; Michael Völkl; Stefanie Corradini; Aurélie V. Gaasch; Annabel H. S. Alig; Thomas Knösel; Christian Hagl; Christian Schneider; et al. (Cardio-Oncology)
Abstract Background Primary cardiac sarcomas (PCS) are rare, aggressive malignancies with poor prognosis and limited evidence guiding optimal management. We aimed to evaluate clinical and histopathological parameters in a single-center PCS cohort. Methods Thirty-three patients diagnosed with PCS between 2002 and 2024 were retrospectively reviewed. Clinical outcomes and prognostic factors were analyzed. Event-free survival (EFS) was defined as the time from initial diagnosis to the first occurrence of disease progression, recurrence, or death. Overall survival (OS) was calculated from initial diagnosis to death. Results The median age at diagnosis was 45 years, with angiosarcoma representing the most common histological subtype (n = 9, 27%). Most patients presented with localized or regional disease (n = 25, 75%), predominantly involving the right (n = 11, 33%) and left atrium (n = 8, 24%). In patients who underwent comprehensive genomic profiling, MDM2 amplification was the most common molecular alteration (n = 5, 45%). The majority of patients received multimodal treatment: surgical resection in 76% (n = 25), systemic therapy in 73% (n = 24), and radiotherapy in 21% (n = 7). After a median follow-up of 63.4 months, median EFS and OS were 11.7 months (95% CI 9.4–23.7) and 37.5 months (95% CI 21.2–83.2), respectively. Distant metastasis (p = 0.027, HR = 3.74) and angiosarcoma histology (p = 0.014, HR = 6.97) were significantly associated with worse OS, while surgical resection was associated with improved OS (p = 0.0064, HR = 0.086). Conclusion Our findings underscore the key clinical and histopathological characteristics of PCS and suggest that surgical resection - even when incomplete - may confer a survival benefit in this aggressive tumor entity. The favorable clinical outcomes observed in this cohort may be attributable to the high proportion of patients undergoing multimodal treatment.